Can Unions Survive? The Rejuvenation of the American Labor Movement - Craver, Charles B. (New York University Press, 1993)
"Defines the challenges facing the movement and offers comprehensive prescriptions for its successful transformation."—The George Washington Law ReviewA valuable analysis of the rise, fall, and--hopefully—the revival of unionism in America. [The book] distills into readable form a mass of legal and empirical analysis of what has been happening in the workplaces of the United States and other industrial democracies. Most important, Craver has drawn a blueprint of what must be done to save collective bargaining in this century—must reading for scholars, lawmakers, and, especially, union leaders themselves.—Paul C. Weiler, Harvard Law SchoolAuthor of Governing the Workplace: The Future of Labor and Employment Law"A thoroughly researched, insightful, and readable look at why American unions have declined. . . .
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jun 2020)
Keywords: BUSINESS & ECONOMICS / Labor; Industrial relations -- United States -- History; Industrial relations; Labor laws and legislation -- United States -- History; Labor laws and legislation; Labor movement -- United States -- History; Labor movement; Labor unions -- United States -- History; Labor unions